Fiqih Zakat Profesi Study Ijtihad Yusuf Al-Qaradawi dan Wahbah Az Zuhayli - Agus Faisal; Ahmad Rofiq (FEBI UIN Sunan Kalijaga, 2026)
Zakat has become a controversial topic of study that is experiencing new ijtihad in the modern era today. Contemporary scholars Yusuf Al-Qaradawi and Wahbah Al-Zuhayli consider professional zakat to be obligatory. However, in terms of how and what is determined, the rulings of the two figures have similarities and differences. This paper uses a library research approach, with content analysis techniques. This method is used to analyze the thoughts of Yusuf Al-Qaradawi and Wahbah Al-Zuhayli related to the law of professional zakat. According to the analysis, the similarity in the thought of professional zakat between Yusuf Al-Qaradawi and Wahbah Al-Zuhayli lies in the permissibility of giving professional zakat; both figures allow the giving of professional zakat although there are certain exceptions. The method of istinbath for professional zakat in Al-Qaradawi's perspective uses qiyas. The use of qiyas in determining professional zakat is analogized with the zakat of gold and silver. Whereas the istinbath method according to Wahbah al-Zuhayli is that professional zakat is not obligatory for every Muslim, because, according to him, there is no strong basis for the existence of professional zakat. However, he provides leniency for those who make professional zakat obligatory.